1)
[tex]-5x^2+3x+2=0\\5x^2-3x-2=0\\x1 = \frac{3+\sqrt{9+40}}{10} = 1\\x2 = \frac{3-\sqrt{9+40}}{10} = -0.4\\ \\[/tex]
2)
[tex]9-6x+x^2=0\\x^2-6x+9=0\\x = \frac{-6+\sqrt{36-36}}{2} = -3[/tex]
3)
[tex]4x^2+5x+1=0\\x1 = \frac{-5+\sqrt{25-16}}{8} = -0.25\\x2 = \frac{-5-\sqrt{25-16}}{8} = -1\\[/tex]
4)
[tex]7x^2+21x-28=0\\x1 = \frac{-21+\sqrt{441+784}}{14} = 1\\x2 = \frac{-21-\sqrt{441+784}}{14} = -4\\[/tex]
5)
[tex]3x^2-24x+45=0\\x1 = \frac{24+\sqrt{576-540}}{6} = 5\\x2 = \frac{24-\sqrt{576-540}}{6} = 3\\[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1)
[tex]-5x^2+3x+2=0\\5x^2-3x-2=0\\x1 = \frac{3+\sqrt{9+40}}{10} = 1\\x2 = \frac{3-\sqrt{9+40}}{10} = -0.4\\ \\[/tex]
2)
[tex]9-6x+x^2=0\\x^2-6x+9=0\\x = \frac{-6+\sqrt{36-36}}{2} = -3[/tex]
3)
[tex]4x^2+5x+1=0\\x1 = \frac{-5+\sqrt{25-16}}{8} = -0.25\\x2 = \frac{-5-\sqrt{25-16}}{8} = -1\\[/tex]
4)
[tex]7x^2+21x-28=0\\x1 = \frac{-21+\sqrt{441+784}}{14} = 1\\x2 = \frac{-21-\sqrt{441+784}}{14} = -4\\[/tex]
5)
[tex]3x^2-24x+45=0\\x1 = \frac{24+\sqrt{576-540}}{6} = 5\\x2 = \frac{24-\sqrt{576-540}}{6} = 3\\[/tex]